STRATEGI INTEGRATED MARKETING COMMUNICATION (IMC) TELKOMSEL DALAM MEMPERTAHANKAN LOYALITAS PENGGUNA TCASH DI PEKANBARU - Agus Tia Ningsih; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
One of the e-money services known by the people of Pekanbaru was T-Cash. Based on the recapitulation of T-Cash users in Pekanbaru increased every month. This condition made PT Telkomsel Pekanbaru hold T-Cash user loyalty in order not to turn to other company. This research was conducted to find out IMC strategy by Telkomsel to maintain T - Cash user loyality and to know the inhibiting factors of T - Cash usage. This research used qualitative method by presented descriptive data analysis and using strategic communication theory. The research technique was chosen based on purposive technique consisted of 1 person ex manager (old manager) YnC T-Cash Pekanbaru, 4 people T-Cash digital staff, 2 partnership and 6 T-Cashdi Pekanbaru users. The Data collection conducted through interview, observation and documentation. The Data analysis techniques used was interactive data models Miles and Huberman. While the examination techniques of data validity included triangulation and extension of participation. The results of the study showed that Telkomsel's Integrated Marketing Strategy (IMC) in maintaining the loyalty of T-Cash users in Pekanbaru was through sales promotion, direct marketing, personal selling, word of mouth marketing, advertisement, event, social media and website, also partnerships and sponsors. Several factors affecting T-Cash user loyalty in Pekanbaru have technical and network constraints, number of human resources and limited number of merchants. Keywords : Integrated Marketing Strategy, promotion, T-Cash.